Unilateral idiopathic retinal vasculitis, aneurysms, and neuroretinitis syndrome (IRVAN) in a young female - MirNaghi Moosavi; Seyedeh Maryam Hosseini; Nasser Shoeibi; Mohammad-Reza Ansari-Astaneh (Journal of Current Ophthalmology, 2015)
Purpose: To report a case of Idiopathic retinal vasculitis, arteriolar macroaneurysms, and neuroretinitis (IRVAN). syndrome in a young female. Case report: A 21-year-old woman presented with unilateral visual acuity (VA) loss. Ophthalmological examination disclosed unilateral optic disc swelling, star-shaped macular exudation, multiple aneurysms surrounded by perivascular exudation, retinal vasculitis, and mild vitreous reaction. The left eye examination was entirely normal. Clinical and paraclinical findings were compatible with IRVAN syndrome criteria. The patient was treated with a short course of oral steroid, a trans-septal triamcinolone acetonide injection, selective laser photocoagulation in peripheral non-perfusion areas, and intravitreal bevacizumab. In spite of primary good response, after each treatment cessation, VA dropped with increasing central macular thickness (CMT), but response to intravitreal triamcinolone (4 mg/0.1 cc) was permanent and good. Conclusion: IRVAN syndrome can have unilateral presentation. All treatment options were temporary except intravitreal steroid injection in our case. The effect of steroid in IRVAN will need further evaluation.